The continuous manufacture of dispersant coated bioresorbable nanoparticles - Walton, Kirsty E. (2018)
This thesis investigates the continuous synthesis and coating of hydroxyapatite nanoparticles (HA NP’s). A range of dispersant molecules were produced and subsequently used in this continuous coating process. Starting with small aliphatic hydrocarbon chains attached to various functional groups a basic understanding of the interactions occurring between the dispersant molecule, the hydroxyapatite surface and a solvent medium was built. It became clear that the length of the hydrocarbon chain, the nature of the functional group and the morphology of the dispersant all had a role to play in the effectiveness and extent of the coating. Using this fundamental understanding the work progressed into the realm of polymeric dispersants. The biodegradable and bioresorbable polymer, polylactic acid (PLA) was utilised in the coating process with the aim of producing HA NP’s that could be dispersed within a polymer matrix. These low molecular weight (Mw) polymers were based on similar chain size and functional groups chemistry. Similar linear morphologies were investigated along with a new six armed, branched morphology. It was concluded that molecular weight of the polymer (chain length), the functional head group (initiator) and morphology of the polymer were all responsible for the dispersant to successfully coat the HA NP’s. However, results indicated that different surface interactions were occurring between the polymeric dispersant chain and HA than those occurring between the hydrocarbon chain and HA. The conclusion that had been drawn from our hydrocarbon coated HA NP’s was that the interaction between dispersant and surface primarily resulted from the functional group. The aliphatic carbon chain would not form any significant surface bonds. This was not the same conclusion drawn from the results of our polymeric dispersants, which appeared to interact favourably with the highly charged nanoparticle surface.